Hybrid-Generative Learning: Learning Outcomes, Creative Thinking Skills, Learning Interest in Islamic Religious Education Subjects in Junior High School - Muhamad Zaini; Agus Purwowidodo; Nuryanti (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose - The purpose of this study is to explain the effect of the Hybrid-Generative Learning implementation on learning outcomes, creative thinking ability, and student learning interest. Desain/methode - This study used a pseudo-experimental method with a nonrandom control design of the pretest-posttest group. The population of this study was all grade 7 students in the even semester at Sekolah Menengah Pertama Negeri (SMPN) 01 Ngunut, Tulungagung. The sample of this study was four (4) classes that were deliberately selected from a total of six (6) classes that attended Islamic religious education subjects. Findings - The average learning outcomes of students in the experimental class were better than those in the control class (67,523 > 57,028). Students in the experimental class had better creative thinking skills compared to the control class (70,387 > 53,633). The average learning interest of students in the experimental class had a higher interest in learning compared to the control class (37,378 > 29,441). The information shows that students who receive Hybrid Generative Learning have learning outcomes, creative thinking skills and learning interests are much higher than students in other classes. Research Implications/limitation - The use of hybrid-generative learning models on other parameters requires further development for future research to reveal positive results on some of the more comprehensive models. Similarly, the duration of time ideally needs to be longer for different learnings. Originality/value - Studies of hybrid-generative learning models have been conducted by several researchers in Indonesia. However, they only focused on developing this model for students' thinking and metacognitive skills. Therefore, this study is genuine, new, and can be a scientific reference.